Monte Carlo simulation to assess free space and end-weld thickness variation effects on dose rate for a new Ir-192 brachytherapy source. (July 2021) - Angelocci, Lucas Verdi; Daruich de Souza, Carla; Pantelis, Evaggelos; Nogueira, Beatriz Ribeiro; Zeituni, Carlos Alberto; Chueri Martins Rostelato, Maria Elisa
Abstract: A new Iridium-192 seed for brachytherapy is under development. Specific dose rate contribution by two different factors were evaluated: the effect from movement of the core in the free space within the seed and the effect of the end-weld thickness variation. Both were investigated through use of the Monte Carlo radiation transport code MCNP6 and an in-house routine programmed with MATLAB. Differences greater than 15% compared to results from the nominal seed were found near the source, indicating a significant dose variation. Graphical abstract: Image 1 Highlights: We are developing an Ir-192 seed for cancer treatment. This seed is currently under dosimetric evaluation. Two factors were investigated: core movement and end-weld thickness variation. Investigated through use of the Monte Carlo - MCNP6 and MATLAB. Differences greater than 15% compared to results from the nominal seed were found.